2015
DOI: 10.3390/molecules20021922
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Four Popular Sweet Cherry Cultivars Grown in Greece by Volatile Compound and Physicochemical Data Analysis and Sensory Evaluation

Abstract: Volatile compounds, physicochemical and sensory attributes of four sweet cherry cultivars (Canada giant, Ferrovia, Lapins and Skeena) grown in Northern Greece were determined. Eighteen volatile compounds were identified and semi-quantified in cherries using solid phase micro extraction in combination with gas chromatography/mass spectrometry (SPME-GC/MS). Carbonyl compounds were the most abundant in sweet cherry aroma, followed by alcohols, esters and hydrocarbons/terpenes. Cherry cultivars in order of increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 33 publications
(68 reference statements)
5
65
1
Order By: Relevance
“…The high relative high content of nonanal (6.9%) as compared to other previous studies [30,31] justifies the intense fruity flavor of the studied cultivars.…”
Section: Volatile Compoundssupporting
confidence: 48%
See 2 more Smart Citations
“…The high relative high content of nonanal (6.9%) as compared to other previous studies [30,31] justifies the intense fruity flavor of the studied cultivars.…”
Section: Volatile Compoundssupporting
confidence: 48%
“…Vavoura et al [30] reported a much lower number of volatile aroma compounds, 18, in the four more popular sweet cherry cultivars grown in Greece; besides, the reported concentrations were lower than the ones found in the Spanish cultivars. However, Serradilla et al [30] reported the contents of up to 81 compounds in cherry cultivars grown in a different Spanish region, Jerte Valley.…”
Section: Volatile Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…reported average levels of Phe from 0.92 to 1.47 mg GAE g −1 FW, Fu et al . reported an average content of 1.14 mg GAE g −1 FW and Vavoura et al . reported a range of 0.95–1.97 mg GAE g −1 FW.…”
Section: Resultsmentioning
confidence: 99%
“…Physicochemical characteristics and antioxidant activities of the 12 varieties of sweet cherries Preliminary sensory analysis was performed according to the method of Vavoura et al (2015) with slight modifications. Fifty healthy panelists (female: 26; male: 24; age: 20-50; non-smokers), who consumed fresh cherries frequently, were recruited locally.…”
Section: Materials and Chemicalsmentioning
confidence: 99%